Recent developments on oximes to improve the blood brain barrier penetration for the treatment of organophosphorus poisoning: a review. Issue 8 (27th January 2020) - Faiz Norrrahim, Mohd Nor; Idayu Abdul Razak, Mas Amira; Ahmad Shah, Noor Aisyah; Kasim, Herdawati; Wan Yusoff, Wan Yusmawati; Halim, Norhana Abdul; Mohd Nor, Siti Aminah; Jamal, Siti Hasnawati; Ong, Keat Khim; Zin Wan Yunus, Wan Md; Knight, Victor Feizal; Mohd Kasim, Noor Azilah
Abstract : Organophosphorus (OP) compounds are highly toxic synthetic compounds which have been used as pesticides and developed as warfare nerve agents. Abstract : Organophosphorus (OP) compounds are highly toxic synthetic compounds which have been used as pesticides and developed as warfare nerve agents. They represent a threat to both military and civilian populations. OP pesticides affect the nervous system and are thought to have caused at least 5 million deaths since their discovery in the 1930s. At present the treatment of OP nerve agent poisoning commonly involves the use of parenteral oximes. However, the blood brain barrier (BBB) remains a challenge in the delivery of oximes to the central nervous system (CNS). This is because almost all macromolecule drugs (including oximes) fail to pass through the BBB to reach the CNS structures. The presence of a permanent cationic charge in oximes has made these compounds inefficient in crossing the BBB. Thus, oximes are unable to reactivate acetylcholinesterase (AChE) in the CNS. Using current structural and mechanistic understanding of the BBB under both physiological and pathological conditions, it becomes possible to design delivery systems for oximes and other drugs that are able to cross the BBB effectively. This review summarises the recent strategies in the development of oximes which are capable of crossing the BBB to treat OP poisoning. Several new developments using oximes are reviewed along with their advantages and disadvantages. This review could be beneficial for future directions in the development of oxime and other drug delivery systems into the CNS.